A cross-sectional study on domestic accidents in the urban field practice area of a private medical college, Davangere, Karnataka - G., Netra; Nawaz, Ayesha S.; Kumar, Aswin; Kusum, Mane; Varadaraja Rao, B. A. (International Journal Of Community Medicine And Public Health, 2017)
Background: The public health experts have coined the name ‘Modern Day Epidemic’ for accidents. Accidents especially domestic are a world-wide public health problem. The relationship between domestic accidents and human health is direct and associated with a chain of socio-economic consequences. The objectives were to study the magnitude and types of domestic accidents in the urban field practice area and to study the healthcare seeking behaviour following domestic accidents. Methods: A community based cross-sectional study was carried out during September 2016 - November 2016 in the urban field practice area of a Medical College in Davangere. A sample size of 2000 was covered by interviewing 366 households. By using pre-designed, pre-tested questionnaire information was collected on basic socio-demographic details, housing conditions, nature and timing of domestic accidents and the health care seeking behaviour. Results: The magnitude of domestic accidents was 5.2%, with falls being the most common domestic accidents (67.2%) occurring during the evening hours. Health seeking behaviour was found to be satisfactory. Conclusions: In our study the domestic accidents were more commonly found in the extreme age groups. Falls were the most frequent type of domestic accidents which occurred during the morning and evening hours, therefore there is a need for adequate lighting during evening hours to prevent dim light as well as proper designing of house to make it elderly and children friendly. The health education should be given regarding necessary safety precautions to reduce the occurrence of domestic accidents.